Species, abundance, time of appearance of fly larvas in white rats (Rattus norvegicus Berkenhout 1769) carcass with different burnt times - Ichsan Luqmana Indra Putra; Muhammad Izzuddin Noor Rahmadi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
The use of insects in determining PMI is still little. The flies during the period of laying eggs and forming larvae can estimate the time of death. This study aims to determine the type, abundance, and time of appearance of fly larvae on white rat carcasses that were treated with burning. The experiment was conducted on 12 female white rats of the wistar strain, aged 2-3 months, healthy, and weighing 150-200 g. The research was experimental which consisted of 4 treatments with 3 repetitions of each treatment. The treatment was given by first anesthetizing the rats using 10% ether, then dislocating the cervical spine. After being sacrificed, the rats were burned using stainless tongs over a fire with variations in burning time, namely A (10 minutes), B (20 minutes), and C (30 minutes). The carcasses of each treatment were placed in an open field with a distance of 2.5 meters between the carcasses. Observations were made for 5 days until the carcass underwent complete decomposition. Larvae were taken from each carcass using tweezers, then put into vials containing 70% alcohol. The larvae were then identified morphologically in the laboratory. There were types of fly larvae found in the burnt treated white rat carcasses, namely Sarcophaga argyrostoma and S. haemorrhoidalis, while the controls were Chrysomya albiceps, C. megacephala, and C. bezziana. S. argyrostoma was found with the highest abundance in the treatment (39.9 individuals), while C. albiceps was found in the control (346.2 individuals). The first fly larvae that appeared in the burning treatment were S. argyrostoma (31 hours) and those of the control C. megacephala (31 hours). The conclusion of this study is that the variation of combustion has or does not affect the type, abundance, and time of appearance of fly larvae on the carcass.